2021
DOI: 10.3389/fimmu.2021.683694
|View full text |Cite
|
Sign up to set email alerts
|

Will Auranofin Become a Golden New Treatment Against COVID-19?

Abstract: Auranofin is an FDA-approved disease-modifying anti-rheumatic drug that has been used for decades for treatment of rheumatoid arthritis. This gold(I) compound has anti-inflammatory properties because it reduces IL-6 expression via inhibition of the NF-κB-IL-6-STAT3 signaling pathway. Also, by inhibiting redox enzymes such as thioredoxin reductase, auranofin increases cellular oxidative stress and promotes apoptosis. Auranofin also possesses antiviral properties. Recently, it was reported that auranofin reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…In fact, this drug was approved for the treatment of rheumatoid arthritis in 1988 and its safety profile is well-known and acceptable; Auranofin is currently under investigation for cancer therapy as a repurposed drug [ 35 ] and has also been proposed to fight a number of bacterial, parasitic and viral infections [ 36 ]. The potential of Auranofin as a drug for the treatment of SARS-CoV-2 recently emerged as a hot topic; a few studies demonstrated its ability to inhibit viral replication by contrasting specific enzymatic activities of the virus [ 5 , 6 , 37 ]. Auranofin could perform its antiviral activity in different ways: one of these is blocking the entry of the virus into the host cell; another is to inhibit the activity of selected viral enzymes that are crucial for virus replication and a last one is to counter host inflammatory response [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, this drug was approved for the treatment of rheumatoid arthritis in 1988 and its safety profile is well-known and acceptable; Auranofin is currently under investigation for cancer therapy as a repurposed drug [ 35 ] and has also been proposed to fight a number of bacterial, parasitic and viral infections [ 36 ]. The potential of Auranofin as a drug for the treatment of SARS-CoV-2 recently emerged as a hot topic; a few studies demonstrated its ability to inhibit viral replication by contrasting specific enzymatic activities of the virus [ 5 , 6 , 37 ]. Auranofin could perform its antiviral activity in different ways: one of these is blocking the entry of the virus into the host cell; another is to inhibit the activity of selected viral enzymes that are crucial for virus replication and a last one is to counter host inflammatory response [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…To this end, expanding the chemical space of the tested compounds by including a large variety of metal compounds is highly desirable. It has to be stressed that the search for efficient inhibitors of SARS-CoV-2-related proteases has almost entirely focused on organic molecules [ 2 , 3 , 4 ]; much less attention has been deserved so far to inorganic moieties [ 5 , 6 ] that merit, in our opinion, a greater consideration.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that auranofin could be potent to limit SARS-CoV-2 infection and associated lung injury due to its antiviral, anti-inflammatory and antireactive oxygen species (ROS) properties. Further in vivo study is required to establish the safety and efficacy of auranofin for the management of SARS-CoV-2 associated disease. , …”
Section: Therapeutic Gold Complexesmentioning
confidence: 99%
“…Auranofin has received considerable attention 20,22,24,114,115 and was shown to inhibit replication of SARS-CoV-2 in human cells (Huh7) with an EC 50 of 1.4 mM. 88 Treatment of SARS-CoV-2 infected cells with auranofin resulted in a 95% reduction in the viral RNA 48 h post-infection.…”
Section: Metal Chelation Based Antiviral Strategymentioning
confidence: 99%
“…auranofin) on inhibition inflammatory pathways and on thiol redox enzymes as well as essential viral enzymes was thought to be responsible at least partially for its anti-SARS-CoV-2 activity. 114,115 The potential inhibition of auranofin on other thiol-containing viral enzymes warrants further studies.…”
Section: Metal Chelation Based Antiviral Strategymentioning
confidence: 99%